PERUBAHAN SISTEM ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) KABUPATEN ROKAN HILIR (DARI SISTEM MATA ANGGARAN LINE ITEM MENUJU MATA ANGGARAN BERBASIS KINERJA) - Yoserizal ' (Jurnal Kebijakan Publik, 2010)
The changing of municipal revenue budget system since 2003 has been made significant changeto the behaviour both of government and employee and legislative member. Traditional budget (line item)that has been used for years, actually had inefficiency and uneffectiveness that finally shows the greedy ofthe budget. The implementation of the budget based on activity, gave many problems and barriers especiallyto the government in Rokan Hilir. This article try describe the problems and the barriers.